If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13-((5*y)/2) = 0
13-((5*Y)/2) = 0
(2/3)*y-1 = 1/4
-((2/3)*m) = -12
(2/3)*y = 0
| -20=-4y+2(y-6) | | 14-1x+2=-6x | | 5-(9-(4+3))= | | 4tan(X)-1=0 | | 6(2x+9)=-72 | | |1/5x-5|-20=0 | | 13-5y/2 | | 3x-4+5x=-39 | | 6a+4b=30 | | 13-5*Y/2 | | √(62.8/5) | | 6y^3-3y^2-18y=0 | | -.33x=3.33 | | 3y^2+22y+60=74y-48 | | 16x^2-128x+252=0 | | 11x-19y=-2 | | 0=5n^2-39n-42 | | 3(-8x+5)=-32x-26 | | (18x+9k)+(2x+6k)=4 | | x^2+7x-27=0 | | -x/5+6=-9 | | 7+x=-33 | | 50=9-r | | x+-5=37 | | f(-3)=0.288571429(-3)+4 | | f(3)=0.288571429(3)+4 | | (x-y^2x)dx+(-yx^2+y)dy=0 | | f(2)=0.288571429(2)+4 | | g(-3)=0.4(-3)+7 | | g(3)=0.4(3)+7 | | 2/3(5/8)-1= | | g(2)=0.4(2)+7 |